Q. 355.0( 2 Votes )

Prove th

Answer :

cos6x  = 4 cos32x - 3 cos2x

          = 4(2cos2x-1)3 - 3(2cos2x-1)

          = 4[(2cos2x)3 - 3×(2cos2x)2×1 + 3 × 2 cos2x×1 - 13]-6cos2x + 3

          = 32cos6x - 48cos4x + 18cos2x -1

          = R.H.S

Hence proved

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses